Non-timber forest products: selected publications from CIFOR - Belcher, B.; Kusters, K.; Suharyanto, G.; Sampurna, Y.; Prianto, E.; Syamsudin, I. (Center for International Forestry Research, 2004)
This CD contains a collection of CIFOR’s key NTFP-related publications. It includes nine books, two journal articles, three working papers and a video. The different publications present a wide variety of information, from chapters focusing on a particular product in a particular village to an article synthesizing global research; from books targeted at civil society to a working paper describing research methods. It will be a valuable resource for people interested in understanding the importance and potential of NTFPs for livelihoods and the environment.